WHISTLEBLOWING INTENTION IN ORGANIZATIONAL JUSTICE & ETHICAL CLIMATE: AN EXPERIMENTAL STUDY - Jonathan Wiyarta Setiawan; Intiyas Utami; David Adechandra Ashedica Pesudo (Jurnal Reviu Akuntansi dan Keuangan, 2020)
Recenty, whistleblowing has become an important subject for organizations because it enables individuals to disclose any regulation’s irregularities and frauds in their organization and report those irregularities and frauds to their superior. Whistleblowing can be supported many factors, among them are organizational justice and ethical climate. Organizational justice consists of distributive justice, procedural justice and interactional justice, while ethical climate consists of egoism, benevolence and principle of ethical climate. This research was conducted to examine employees’ tendencies to show their whistleblowing intentions when faced with organizational justice and ethical climate. Laboratory study was used as the type of this research that was administered at one of private universities in Yogyakarta and this research used 115 bachelor students majoring in accounting as the subjects of this research and generated 63 usable data. This research used 3x3 between subjects experiment as the design of the research and manipulated organizational justice and ethical climate. The results show that subjects who experienced distributive justice and benevolence of ethical climate had higher employees’ tendencies to show whistleblowing intentions than subjects who experienced procedural justice and interactional justice and ethical climate of egoism and ethical climate of benevolence .